∫ − π π 1 + cos 2 x 2 x ( 1 + sin x ) d x = π m , m = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let me present an alternative solution that doesn't use IBP and instead uses simple trigonometric substitution later on. We use a particular property of definite integrals, namely: a ∫ b f ( x ) d x = a ∫ b f ( a + b − x ) d x
Moving on to the problem, consider the integral as I . Using the property mentioned above, we have,
I = − π ∫ π 1 + cos 2 x 2 x ( 1 + sin x ) d x = − − π ∫ π 1 + cos 2 x 2 x ( 1 − sin x ) d x ⟹ 2 I = − π ∫ π 1 + cos 2 x 2 x ( 1 + sin x − 1 + sin x ) d x ⟹ 2 I = − π ∫ π 1 + cos 2 x 4 x sin x d x
Now, this integrand is even and hence, we can simplify it as,
2 I = 2 ⋅ 0 ∫ π 1 + cos 2 x 4 x sin x d x ⟹ I = 0 ∫ π 1 + cos 2 x 4 x sin x d x
Using the property mentioned at the very beginning, the integral can be written as,
I = 0 ∫ π 1 + cos 2 x 4 π sin x − I ⟹ 2 I = 4 π ⋅ 0 ∫ π 1 + cos 2 sin x d x
Make the substitution t = ( − cos x ) and d t = sin x d x to get,
2 I = 4 π ⋅ − 1 ∫ 1 1 + t 2 d t
This integrand is again even and also we can easily identify the integrand to be the derivative of arctan t . Hence, we have,
2 I = 8 π ⋅ [ arctan t ] 0 1 = 8 π ( 4 π − 0 ) ⟹ I = π 2
@kritarth lohomi , Problem? :3
Log in to reply
I solved the same way too .
No, never, nakku, ille!!
The limits are from π to π . Isn't the answer zero?
Log in to reply
If you spot any errors with a problem, you can “report” it by selecting "report problem" in the “dot dot dot” menu in the lower right corner. That will allow the problem creator to be notified, and they can fix this problem.
Can anyone please check? I could not try the question. @ @Calvin Lin
Problem Loading...
Note Loading...
Set Loading...
Our integral can be represented as:
I = ∫ − π π 1 + cos 2 x 2 x d x + ∫ − π π 1 + cos 2 x 2 x sin x d x
The first integral is zero ( integrand is odd function and see the integration limits) . Use Integration by parts in the second integral , with u = 2 x and d v = 1 + cos 2 x sin x d x :
d u = 2 d x , v = − arctan ( cos x )
= > I = − 2 x arctan ( cos x ) ∣ − π π + 2 ∫ − π π arctan ( cos x ) d x
I = π 2 + 4 ∫ 0 π arctan ( cos x ) d x − − → ( 1 )
I = π 2 + 4 ∫ 0 π arctan ( cos ( π − x ) ) d x ( x → ( π − x ) )
I = π 2 − 4 ∫ 0 π arctan ( cos x ) d x − − → ( 2 )
Add ( 1 ) and ( 2 ) :
2 I = 2 π 2 = > I = π 2